Unexpected failures to control chagas disease vectors with pyrethroid spraying in Northern Argentina - Gurevitz, Juan Manuel (2012)
Effectiveness of the elimination efforts against Triatoma infestans (Klug) in South America through residual application of pyrethroid insecticides has been highly variable in the Gran Chaco region. We investigated apparent vector control failures after a standard community-wide spraying with deltamethrin SC in a rural area of northeastern Argentina encompassing 353 houses. Insecticide spraying reduced house infestation less than expected: from 49.5% at baseline to 12.3 and 6.7% at 4 and 8 mo postspraying, respectively. Persistent infestations were detected in 28.4% of houses, and numerous colonies with late-stage bugs were recorded after the interventions. Laboratory bioassays showed reduced susceptibility to pyrethroids in the local bug populations. Eleven of 14 bug populations showed reduced mortality in diagnostic dose assays (range, 35 ± 5% to 97 ± 8%) whereas the remainder had 100% mortality. A fully enclosed residual bug population in a large chicken coop survived four pyrethroid sprays, including two double-dose applications, and was finally suppressed with malathion. The estimated resistance ratio of this bug population was 7.17 (range, 4.47-11.50). Our field data combined with laboratory bioassays and a residual foci experiment demonstrate that the initial failure to suppress T. infestans was mainly because of the unexpected occurrence of reduced susceptibility to deltamethrin in an area last treated with pyrethroid insecticides 12 yr earlier. Our results underline the need for close monitoring of the impact of insecticide spraying to provide early warning of possible problems because of enhanced resistance or tolerance and determine appropriate responses.